2021
DOI: 10.3390/su14010390
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Methodological Intervention for Developing Respect, Inclusion and Equality in Physical Education

Abstract: The following educational intervention proposal arises from the importance of implementing an education based on fostering values through physical education (PE) lessons. PE has certain characteristics that contribute to enhancing learning at a social, affective and psychological level, in addition to promoting adequate physical development. The proposed design is based on Donald Hellison’s personal and social responsibility model (TPSR), whose main objective is to achieve a teaching methodology that can conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…Keleş & Yoncalık (2019) determined that secondary school students acquired the values of courageleadership, responsibility, respect, friendship, justice, self-confidence, helpfulness, Ataturkism, patriotism, hard work, and empathy at a very good level in physical education and sports lessons. Similarly, Muñoz-Llerena et al, (2022) concluded that the students who follow the physical education lesson are capable of respecting individual differences, standing up against obstacles, and enabling their learning. Related studies support the findings of the study.…”
Section: Value Perceptionmentioning
confidence: 99%
“…Keleş & Yoncalık (2019) determined that secondary school students acquired the values of courageleadership, responsibility, respect, friendship, justice, self-confidence, helpfulness, Ataturkism, patriotism, hard work, and empathy at a very good level in physical education and sports lessons. Similarly, Muñoz-Llerena et al, (2022) concluded that the students who follow the physical education lesson are capable of respecting individual differences, standing up against obstacles, and enabling their learning. Related studies support the findings of the study.…”
Section: Value Perceptionmentioning
confidence: 99%
“…When promoting the transformation of learners' SoRL from weak SoRL to progressive SoRL, teachers should focus on strengthening learners' CM and increasing learners' sense of belonging to the team. For example, teachers should establish a collaborative atmosphere of respect, equality, and tolerance, encourage learners to speak freely in the collaborative process, and provide sufficient learning resources for the collaborative process to facilitate learners' discussion of learning resources [56]. In addition, teachers should guide collaborative groups to establish a promotive goal structure.…”
Section: Practical Inspirationmentioning
confidence: 99%
“…The physical education program has its own specificity, which promotes comprehensive physical development and helps improve learning in social, emotional, and psychological aspects. Adopting a variety of sports at the learning stage provides an effective way of educating young people who are at risk and promotes the development of respect, equality and inclusion in this work [15]. Wu, G et al point out that the blended teaching model, which combines traditional classroom and online learning, has gained the attention and importance of teachers and students.…”
Section: Introductionmentioning
confidence: 99%